A napi ingázás feltételei és a heyi munkanélküliség Magyarországon: Újabb számítások és számpéldák - János Köllő (Hungarian Academy of Sciences, Institute of Economics, 2006)
– The paper analyses how the municipality-level unemployment rates of 1993 and their changes in 1993-2001 were affected by the availability of urban labour markets in Hungary. The year 1941 share of the Jewish population is used as an instrument for availability, in order to mitigate endogeneity, which arises because common unobserved factors may simultaneously affect unemployment and public transport connections. Compared to previous OLS results the effect of availability appears to be stronger. The unemployment rate differentials between integrated and remote municipalities have been increasing since 1993.
Keywords: J61; J69; R69; 330; Geographical Labour Mobility; Commuting; Regional Economic Activity; Arbeitsmobilität; Pendelverkehr; Transportkosten; Regionaler Arbeitsmarkt; Städtischer Arbeitsmarkt; Ungarn